Water Service Management in Island Communities: Analysis of Community Participation and Local Policies in Ay Island, Banda, Maluku Province - Paulus Koritelu (Jurnal Manajemen Pelayanan Publik, 2024)
This research proposes to analyze water service management in Ay Island, Banda, Maluku Province, with a focus on community participation and the implementation of local policies. The study employs a qualitative approach and a case study method. The research findings indicate that the local government has successfully implemented water service management through policies covering planning, organizing, directing, and supervising in managing of water resources in the Ay Island region. In the context of planning, the identification of potential water sources, resource allocation, and the development of water infrastructure come to be the main focus, demonstrating a commitment to ensuring water availability for agriculture and community requirements. Furthermore, the crucial role of community participation in water management in Ay Island, progressing from lower to higher levels on Arnstein's ladder, reflects a positive transformation from symbolic involvement to full empowerment of the community in water-related decision-making. Through practices such as rainwater harvesting and dam construction, Ay Island embodies the concept of sustainability, encompassing ecological, economic, and social aspects, creating a model for water management that can serve as inspiration for other island regions facing similar challenges.